Reconstituting the strategies of sustainable stormwater management - Mohd Faiz Musa,; Ismawi Hj. Zen,; Izawati Tukiman, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Sustainable stormwater management strategies such as stormwater wetland, swale, porous pavement and green roof are about the replication of hydrology cycles to reduce quantity and to improve the quality of stormwater through stormwater infrastructures. There are many strategies available, however, little discussion on the relationship of the strategies with the hydrology cycles made the implementation less successful in managing the problem caused by stormwater such as flash flood and water pollution. Hence, this research aims to review the strategies of sustainable stormwater management. Two objectives formulated are (i) to identify the strategies of sustainable stormwater management, and (ii) to identify the relationship of the identified strategies with hydrology cycles. Online journal, forum discussion and e-mail interview were used as methods of data collection in this qualitative research. Five steps of descriptive comparative analysis were used to analyse the data. Consequently, the researcher had identified 18 strategies and listed the strategies in priority order. The 18 strategies are urban stream reclamation, tree canopy cover, change impervious to pervious cover, vegetated surface channel, rainwater harvesting, stream daylighting, infiltration basin, disconnection of impervious area, green roof, modification of soil, stormwater wetland and bioretention pond, barrier system, narrow street, rain garden and greenway. The identified strategies were listed in priority order based on relationship with seven hydrology cycles, which are interception, infiltration, surface runoff, depression storage, evapotranspiration, groundwater flow and interflow. The strategies were analysed with hydrology cycles to ensure the sustainability factors in listing the strategies to manage the stormwater.